THE FUNCTION OF CREDIT IN THE GROWTH OF SMALL AND MEDIUM BUSINESSES - Karimjonov Doniyorbek Ibrohimjon O’g’li (International Journal of Business, Law and Political Science, 2025)
Objective: The article aims to examine the role of credit in the development of small and medium enterprises (SMEs) and its broader impact on economic development. It focuses on understanding the importance of banking credit in a market economy and comparing key concepts related to credit functions. Method: A comparative analysis is conducted between the concepts of "role of credit" and "function of credit." The article reviews various academic perspectives on these concepts, critically analyzing and synthesizing the opinions of different authors. Additionally, it explores several functions of credit, including its redistribution and the role of credit operations in replacing real money. Results: The analysis reveals that credit plays a pivotal role in the economic development of SMEs, acting as a catalyst for growth and operational sustainability. The functions of credit, including redistribution and facilitating transactions without physical money, are essential for maintaining liquidity and promoting economic stability. Novelty: This study provides a critical analysis of existing theories on credit, offering new insights into the interplay between credit functions and its economic significance. By presenting a comprehensive view, it contributes to a better understanding of how credit can influence the growth of SMEs and economic development as a whole.